PERTANGGUNGJAWABAN PIDANA APARATUR SIPIL NEGARA (ASN) YANG MELAKUKAN TINDAKAN PEDOFILIA TERHADAP ANAK DI LINGKUNGAN SEKOLAH DASAR TIMOR TENGAH UTARA SERTA PERLINDUNGAN TERHADAP ANAK SEBAGAI KORBAN - Manubulu, Cristin Octavia; Sinurat, Aksi; Fanggi, Rosalind Angel (Petitum Law Journal, 2024)
Criminal responsibility means that every person who commits a criminal offense or against the law, as formulated in the law, then that person should be held accountable for his actions in accordance with his guilt. Criminal responsibility is determined after there is a criminal offense. To be held criminally responsible, a person must first prove that he has fulfilled all the elements of the criminal offense charged to him. This research is an empirical legal research, which examines and analyzes data obtained from the research location.This research was conducted at the Kefamenanu District Court. Data processing is carried out with data obtained both primary data and secondary data and analyzed based on the formulation of problems that have been applied. The results of this study indicate that (1) the perpetrator defendant fulfills the four conditions of criminal responsibility, namely the existence of a criminal act, the element of guilt, the existence of a responsible maker, there is no excuse so that he is punishable in Article 82 paragraph (2) of the Law of the Republic of Indonesia Number 35 of 2014 concerning amendments to the Law of the Republic of Indonesia Number 23 of 2002 concerning Child Protection Jo. Article 65 paragraph (1) of the Criminal Code, therefore the Chief Judge sentenced the defendant to 20 (twenty) years imprisonment and a fine of Rp.100.000.000,- (one hundred million rupiahs). (2) the protection of child victims is very important to ensure that their rights are fulfilled and they get proper justice by providing legal assistance or assistance from the police investigation to the court, which can be provided by the Consultation and Legal Aid Institute or institutions such as the Indonesian Child Protection Commission (KPAI) and the Witness and Victim Protection Agency (LPSK), conducting a post mortem at the hospital and laboratory examinations according to the direction of medical personnel and asking for psychologist assistance. Apart from the police, there are also institutions that cooperate in protecting victims, namely the Social Service Unit of the Indonesian Ministry of Social Affairs.